Economic damage associated with excess salt intake of Russian people in 2016 - Yu. A. Balanova; A. V. Kontsevaya; A. O. Myrzamatova; D. K. Mukaneeva; M. B. Khudyakov (Кардиоваскулярная терапия и профилактика, 2019)
Previous world studies proved the associations between excess salt intake and the risk of chronic non-communicable diseases (CNCD). Excess salt intake is a significant behavioral risk factor (RF), having a high prevalence in the Russian Federation (49,9%). The assessment of the economic damage (ED) of the RF is a significant cause for investment in its correction.Aim. To assess the ED of excess salt intake in the Russian Federation in 2016, including the direct costs of the health care system and economic waste due to morbidity and mortality from CNCD associated with salt intake. Material and methods. Based on information on the prevalence of excess salt intake and relative risks (RR), according to meta-analyzes and large studies, we calculated population attributable risk (PAR) for cardiovascular diseases (CVD), stroke, type 2 diabetes (T2D), stomach cancer. To assess the ED, we determined share of RF in the morbidity and mortality from CNCD, and then PAR was calculated. We used data from the Federal State Statistics Service, parameters of Annual Forms of Federal Statistical Monitoring, the results of Program of state guarantees for free medical care and the corresponding diagnosis-related groups for 2016. The ED associated with excess salt intake was calculated on the basis of its prevalence in the Russian population based on the ESSE-RF population study — 49,9%. The calculations were performed in Microsoft Excel 10.0. Results. The calculated PAR, associated with excess salt intake, for CVD mortality and morbidity was 5% and 7% respectively; for stroke: in mortality — 17%, in morbidity — 10%. For T2D PAR in the morbidity was ~18%, for stomach cancer — 7%. In the top of direct medical costs associated with excess salt intake were CVD expenses (>15 billion rubles), of which >3 billion accounted for by stroke. All direct medical costs in 2016 exceeded 19 billion. The ED associated with the excess salt intake exceeded 160,9 billion rubles in 2016, i.e. 0,19% of the gross domestic product of Russian Federation for the analyzed year. The largest contribution of excess salt intake is in the damage associated with CVD (122,8 billion rubles), where half (68,1 billion rubles) is attributable to the ED associated with stroke. In the structure of the ED of each nosology, excess salt intake cause from 4,5% (CVD in general) to 17% (for T2D) and 16,1% (stroke) of the entire damage.Conclusion. The calculations of ED from CNCD are extremely demanded today; they serve to justify the introduction of population prevention measures in the country, assess and model the effectiveness of such measures in the complex or their components.